Principles of chemical engineering processes : Material and energy balances - Ghasem, Nayef (Chemical engineering, 2015)
Introduction - Process units and degrees of freedom analysis - Material balance on single-unit process - Multiunit process calculations - Material balances on reactive systems - Multiple-unit systems involving reaction, recycle and purge - Single and multiphase systems - Energy and energy balances - Energy balance with reaction - Simultaneous material and energy balances - Unsteady-state material and energy balances - Appendix.